Trade Effects of Regional Standards Liberalization : A Heterogeneous Firms Approach - Baller, Silja (The World Bank, 2007)
This study investigates trade effects of the regional liberalization of technical barriers to trade (TBTs) in the form of harmonization and mutual recognition agreements (MRAs) for testing procedures. The theoretical part of the paper is framed in terms of a heterogeneous firms approach. This paper adds to the existing literature by formalizing the effects of MRAs and harmonization initiatives on bilateral trade flows and by applying this new theoretical framework in the empirical part of the paper. The latter consists of a two-stage gravity estimation and investigates sectoral effects of TBT liberalization on parties to the agreement as well as excluded industrial and developing countries. It finds that MRAs have a strong positive influence on both export probabilities and trade volumes for partner countries. Regarding harmonization, results seem to suggest that the impact on parties to the agreement is negligible, however that on excluded OECD countries is large and positive. Third party developing countries do not seem to benefit from the market integration effect brought about by harmonization in other regions. Overall, effects on the probability that a new firm will export are much more pronounced than effects on the trade volumes of incumbent exporters